2006
DOI: 10.1007/s00439-006-0259-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of preeclampsia: paradigm shifts

Abstract: Segregation of preeclampsia into early-onset, placental and late-onset, maternal subtypes along with the acknowledgement of the contribution of epigenetics in placentally expressed genes proved to be a key first step in the identification of essential gene variants associated with preeclampsia. Application of this insight to other populations and related pregnancy-induced syndromes, such as HELLP, and acknowledgment of the features shared between chromosomal loci associated with preeclampsia in different popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 31 publications
4
63
0
1
Order By: Relevance
“…Furthermore, Rahimi et al (2013) confirmed that the ACE D allele and DD genotype were more associated with increased risk of mild preeclampsia (1.99-and 2.34-fold respectively) than severe preeclampsia (1.61-and 1.56-fold respectively), similar to the results of the study by Mandò et al (2009). These results substantiated the theory that severe and mild preeclampsia patients are characterized by genetic heterogeneity (Oudejans et al 2007). Furthermore, they demonstrated that the ID genotype of ACE is associated with lower total antioxidant capacity levels compared with the II genotype, which suggested the lipid peroxidation and oxidative stress, known to be involved in the pathogenesis of preeclampsia, and this might be influenced by polymorphisms in the genes.…”
Section: Ace Polymorphism In Preeclampsiasupporting
confidence: 81%
“…Furthermore, Rahimi et al (2013) confirmed that the ACE D allele and DD genotype were more associated with increased risk of mild preeclampsia (1.99-and 2.34-fold respectively) than severe preeclampsia (1.61-and 1.56-fold respectively), similar to the results of the study by Mandò et al (2009). These results substantiated the theory that severe and mild preeclampsia patients are characterized by genetic heterogeneity (Oudejans et al 2007). Furthermore, they demonstrated that the ID genotype of ACE is associated with lower total antioxidant capacity levels compared with the II genotype, which suggested the lipid peroxidation and oxidative stress, known to be involved in the pathogenesis of preeclampsia, and this might be influenced by polymorphisms in the genes.…”
Section: Ace Polymorphism In Preeclampsiasupporting
confidence: 81%
“…Genetic factors are thought to have a role in getting the disease [18,19]. Observations that suggest this are that women who are pregnant for the first time and have a family history of preeclampsia have a higher risk of getting it than women who are pregnant for the first time and do not have a family history of preeclampsia [20].…”
Section: Genetic Factorsmentioning
confidence: 99%
“…1 Clinical observations suggest that earlyonset and late-onset disease types can be separated in origin, even though individual cases share characteristics. 3 The progression of the disease is unpredictable and may lead to a convulsive phase, eclampsia. The removal of the affected placenta through delivery is the only known treatment for pre-eclampsia.…”
Section: Introductionmentioning
confidence: 99%